2022
DOI: 10.3390/pr10030525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanol Application on Carbon Emissions and Pollutant Emissions Using a Passenger Vehicle

Abstract: Methanol, as a promising carbon-neutral fuel, has become a research hotspot worldwide. In this study, pure gasoline and gasoline blended with five different volume ratios of methanol (10%, 20%, 30%, 50%, and 75%) were selected as test fuels, which were referred to as M0, M10, M20, M30, M50, and M75. The experiments on carbon and pollutant emissions and performance were carried out on a passenger vehicle with gasoline direct injection (GDI) turbocharged engine using the steady-state, new European driving cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Gong et al [16] and Cui et al [17] found that increasing the temperature in the engine cylinder is the dominant factor to ensure the stable ignition of the direct injection methanol fuel in the cylinder. Wang et al [18] studied different types of preheating systems to enable the methanol ignition engine to start smoothly at the ambient temperature of −10 • C. Liu et al [19] found that increasing the intake air heating temperature to 120 • C can ensure the smooth start of a heavy-duty multi-cylinder diesel engine fuelled by methanol at a cooling water temperature of 30 • C.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [16] and Cui et al [17] found that increasing the temperature in the engine cylinder is the dominant factor to ensure the stable ignition of the direct injection methanol fuel in the cylinder. Wang et al [18] studied different types of preheating systems to enable the methanol ignition engine to start smoothly at the ambient temperature of −10 • C. Liu et al [19] found that increasing the intake air heating temperature to 120 • C can ensure the smooth start of a heavy-duty multi-cylinder diesel engine fuelled by methanol at a cooling water temperature of 30 • C.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a passenger vehicle equipped with a GDI turbocharged engine emits 5.46 g/km (3.7% less) of CO 2 than pure gasoline when tested with 30 vol% methanol added fuel in the NEDC [ 29 ]. Blending 20% n-butanol into gasoline reduces CO 2 emissions by 5.7% compared to gasoline [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Methanol is an alternative fuel that offers lower CO emissions and higher efficiency. Methanol comes from biomass [5]. In addition to reducing CO, methanol fuel does not produce soot when burning in the combustion chamber, so the NOx content in the exhaust gas is not large.…”
Section: Methanol (Ch3oh) [3]mentioning
confidence: 99%